Three new species of the genus Paradoxecia Hampson, 1919 (Lepidoptera: Sesiidae) from China - Yu, Tiantian; Arita, Yutaka; Kallies, Axel; Wang, Min (Zootaxa, 2019)
Three new species of the genus Paradoxecia Hampson, 1919 (Lepidoptera: Sesiidae) are described from China: Paradoxecia kishidai Yu & Arita sp. nov., Paradoxecia polyzona Yu & Kallies sp. nov. and Paradoxecia beibengensis Yu & Kallies sp. nov. Illustrations of the holotypes and the male genitalia are provided along with a key to all currently known species of the genus. DNA barcodes of the new species are deposited in Genbank.